Structural Behaviour of Reinforced Concrete Beam with Embedded Polystyrene Spheres - Ling, Jen Hua; Lau, Ji Wei; Lim, Yong Tat (Civil and Sustainable Urban Engineering, 2023)
The beam is a structural element in a reinforced concrete structure. However, its weight places additional strain on the columns and foundations.Polystyrene spheres can be used to replace concrete in a beam to reduce its weight. However, this can affect the beam’s structural performance. This study investigated the behavior of beams with embedded polystyrene spheres under loads. The purpose was to determine the feasibility of this technique. Six beam specimens, including a control specimen, were tested under the four-point load setup. The polystyrene spheres’ diameter ranged from 50 mm to 75 mm. The spacing between the spheres varied from 10 mm to 30 mm. By replacing 8.7% of the concrete, the beam's strength increased by 8% per unit of concrete. The polystyrene spheres marginally altered the load capacity but reduced the stiffness, uncracked load, and ductility. The load capacity decreased by 2.6% as the polystyrene sphere’s diameter increased from 50 mm to 10 mm. The strength increased by 0.6% as the spacing increased from 10 mm to 30 mm. For satisfactory performance, the polystyrene spheres with a diameter of 0.57 times the beam’s width may be spaced at 1.2 times the concrete cover.